Through the gateway: reporting on collections - Hurd, Sandy; Feick, Tina; Smith, John; Simser, Charlene N. (My University, 2012)
Librarians are frequently required to support collection and broader management decisions. Line staff and managers need clear and complete data that can be easily accessed and manipulated in order to understand current and historic situations and trends. Presentation of that data must be visually compelling and easily used to support reporting to administrators, funders, and accrediting bodies. The presenters discussed the reports development process, the need for dialogue amongst stakeholders not only to retrieve useful data but also to analyze it, and provided examples of a variety of collections-related reports.
Keywords: Collections; Statistics; Collection development; Reporting tools